THE CHARACTERS OF KUPFFER CELLS LIVING IN VITRO - Beard, J. W. (The Rockefeller University Press, 1934)
The Kupffer cells procured from the liver of the rabbit and dog for culture in vitro have the typical characters of clasmatocytes. They are readily discriminated from the monocytes washed from the liver with them; and they have certain peculiar features which suffice to differentiate them from some at least of the clasmatocytes of other organs. Their surface is extraordinarily sticky,—far more so than that of blood leukocytes or of the clasmatocytes found in peritoneal exudates; and in consequence they are exceedingly difficult to handle in vitro. They put forth enormous, pellucid, circular membranes resembling those of exudate clasmatocytes but larger. Splenic clasmatocytes, on the other hand, put forth rather small, one-sided ground-glass membranes like broad tongues. On comparing them with Kupffer cells and exudate clasmatocytes one perceives that they are not wholly identical in their characters, but have secondary peculiarities. However, there exist good morphological reasons for grouping them together and terming them all reticulo-endothelial. Kupffer cells are notably sensitive to injury, surviving in Tyrode solution for a much shorter time than blood leukocytes. However, they can be readily cultured on lens paper in serum. Under such circumstances they scatter on the fibres and live separately, presenting the same general aspect as when in the liver; but in the course of proliferation they soon lose some of their pronounced characters, retaining such as are common to clasmatocytes in general. A considerable population of ordinary leukocytes exists in the hepatic sinuses over and above those circulating in the blood. During infection, their number may greatly increase. Several cubic centimeters of packed white cells have been obtained from the liver of a sick dog. The fact has been realized that leukocytes may stop a while in the liver, yet the extent of the accumulation which sometimes takes place seems deserving of stress.